THE IMPACT OF PERCEPTION OF PRECEPTORSHIP IN NURSING: AN ARTICLE REVIEW (Academicia Globe: Inderscience Research, 2022)
Preceptorship is a frequent practical education approach for new nurses, and opinions about it vary and originate from a variety of sources. The purpose of this study was to explore the effective qualities of nursing preceptorship. Methods: The outcomes of the article review were attained by selecting publications that explicitly connected to preceptorship as well as those that studied the most beneficial qualities linked with clinical precepting.